(untitled) (مجلة البحوث الأكاديمية, 2026)
Integrated multi-biomarker profiling provides critical insights into subclinical metabolic disturbances. A retrospective, cross-sectional archive analysis was conducted utilizing laboratory records from Zawia Medical Centre (N=208). Ten biomarkers across five physiological axes were quantified. To address real-world missing data, pairwise deletion was applied. Inter-system cross-talk was calculated via Pearson correlation coefficients (r) using IBM SPSS (v26.0). The cohort exhibited glycaemic stress with an elevated mean Fasting Blood Sugar of 119.95 pm 46.38 mg/dL (n=133, Range: 29–370 mg/dL). Renal filtration markers showed marked dispersion: serum urea averaged 25.78 pm 11.25 mg/dL (n=109) and serum creatinine stood at 0.83 pm 0.85 mg/dL (n=92), skewed by advanced nephropathy outliers (Max: 8.50 mg/dL). Bivariate analysis exposed highly synchronized intra-hepatic activity between ALT and AST (r=0.834, P=0.003, n=10). Crucially, a distinct inter-system feedback loop linked macromineral stability with enzymatic pathways, where serum calcium (9.26 pm 1.33 mg/dL, n=61) correlated positively with Alkaline Phosphatase levels (r=0.460, P=0.041, n=20). Additionally, a significant musculoskeletal-renal filtration interface connected categorical Creatinine Status with circulating Creatine Kinase (r=0.958, P=0.042, n=4). Gender (66.3% female, 33.7% male) demonstrated complete biochemical uniformity across all axes (P>0.05). Correlated variations across glycaemic, renal, hepatic, and mineral biomarkers suggest the presence of interconnected metabolic disturbances rather than isolated physiological alterations. These findings provide valuable real-world evidence from western Libya and highlight the importance of strengthening standardized electronic laboratory databases to support regional screening strategies, disease surveillance, and chronic disease prevention efforts.